PENGARUH SUBSTITUSI HAY RUMPUT KUME DENGAN HAY FODDER JAGUNG TERHADAP TINGKAH LAKU MAKAN KAMBING KACANG (The Effect of Substituting Kume Grass Hay with Maize Fodder Hay on Feeding Behavior of Kacang Goats) - Bahas, Aldi Seprianus; Jelantik, I Gusti Ngurah; Benu, Imanuel (Universitas Nusa Cendana, 2025)
This study aimed to investigate the effect of substituting Kume Grass hay with maize fodder hay on the feeding behavior of Kacang Goats. Eight goats weighing 10–15 kg were used in a change-over design with four treatments and two periods as replicates. The treatments were: DMF0 (70% Kume Grass hay + 30% concentrate), DMF1 (52.5% Kume Grass hay + 17.5% maize fodder hay + 30% concentrate), DMF2 (35% Kume Grass hay + 35% maize fodder hay + 30% concentrate), and DMF3 (17.5% Kume Grass hay + 52.5% maize fodder hay + 30% concentrate). Data were analyzed using ANOVA followed by Duncan’s multiple range test. Results showed that feeding time ranged from 4.5 to 7.0 hours/day, eating frequency from 6.3 to 12.8 times/day, rumination time from 3.6 to 5.1 hours/day, rumination frequency from 10.1 to 19.6 times/day, resting time from 13.1 to 14.5 hours/day, and resting frequency from 17.1 to 21.8 times/day. Statistical analysis revealed that the treatments significantly (P<0.05) affected feeding time, eating frequency, and resting frequency, but had no significant effect (P>0.05) on rumination time, rumination frequency, and resting time. In conclusion the substitution of Kume Grass hay with maize fodder hay up to 75% the eating duration, eating frequency and resting frequency, but it does not affect the rumination duration, rumination frequency and resting duration.